2019
DOI: 10.1089/cbr.2018.2654
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of HER2 with [89Zr]pertuzumab in Response to T-DM1 Therapy

Abstract: Background: The success of human epidermal growth factor receptor 2 (HER2)-targeted therapy depends on accurate characterization of HER2 expression, but current methods available have several limitations. This study aims to investigate the feasibility of [ 89 Zr]pertuzumab imaging to monitor early response to Adotrastuzumab emtansine (T-DM1) therapy in mice bearing xenografts of HER2-positive breast cancer (BCa). Materials and Methods: Pertuzumab was conjugated to DFO-Bz-NCS and labeled with 89 Zr. Mice bearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 33 publications
1
24
0
1
Order By: Relevance
“…We have recently shown that high HER2 expression is associated with aggressive disease and poor survival in EC [41]. 89 Zr-labeled pertuzumab ( 89 Zr-pertuzumab) has been used to detect HER2-positive breast cancer in small human cohorts [42,43] and to delineate tumors and show treatment effects from trastuzumab-emtansine (T-DM1) in HER2-positive breast cancer xenografts [44]. Similarly, PET-CT with radiolabeled pertuzumab ( 64 Cu-NOTA-pertuzumab) was used for non-invasive detection and monitoring of HER2 tumor expression, enabling the detection of primary tumors and peritoneal metastases in both subcutaneous and orthotopic models of ovarian cancer [45].…”
Section: Radioligands For Visualization Of Target-specific Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that high HER2 expression is associated with aggressive disease and poor survival in EC [41]. 89 Zr-labeled pertuzumab ( 89 Zr-pertuzumab) has been used to detect HER2-positive breast cancer in small human cohorts [42,43] and to delineate tumors and show treatment effects from trastuzumab-emtansine (T-DM1) in HER2-positive breast cancer xenografts [44]. Similarly, PET-CT with radiolabeled pertuzumab ( 64 Cu-NOTA-pertuzumab) was used for non-invasive detection and monitoring of HER2 tumor expression, enabling the detection of primary tumors and peritoneal metastases in both subcutaneous and orthotopic models of ovarian cancer [45].…”
Section: Radioligands For Visualization Of Target-specific Expressionmentioning
confidence: 99%
“…xenografts (BT-474) including evaluation of tumor size change after treatment with HER2-targeted antibody-drug conjugate (T-DM1) [44]. 64 Cu-NOTA-pertuzumab…”
Section: Radioligands For Visualization Of Target-specific Expressionmentioning
confidence: 99%
“… 10 Currently in phase II clinical trials, the 89 Zr radiolabeled antibody is injected and requires a 4-7 day post-injection imaging time. 10 , 11 The long imaging time points, due to the circulation time of the antibody, can create logistic challenges for both patients and facilities. To pair with the biological half-life and optimal scanning time for the antibodies, longer-lived isotopes must be used which increases the amount of radiation exposure to both the patients and the personnel involved in the synthesis of the radiopharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…However, the invasive method may not be reliable because the HER2 expression is heterogeneous in the tumors and varies during the progress of the disease [9]. Almost 20% of the outcomes was inaccurate [10].…”
Section: Introductionmentioning
confidence: 99%